Ela E. Gezen. Brecht, Turkish Theater, and Turkish-German Literature. Reception, Adaptation, and Innovation after 1960. Camden House, 2018. - Lydia J. White (Studies in 20th & 21st Century Literature, 2019)
Review of Ela E. Gezen. Brecht, Turkish Theater, and Turkish-German Literature. Reception, Adaptation, and Innovation after 1960. Camden House, 2018. 159 pp.
Keywords: Review; Gezen; Brecht; Turkish Theater; Turkish-German Literature